2013
DOI: 10.1080/00222933.2013.770101
|View full text |Cite
|
Sign up to set email alerts
|

Spatial characterization of megabenthic epifauna of soft bottoms around mud volcanoes in the Gulf of Cádiz

Abstract: The structure and composition of megabenthic epifauna from the mud volcano field known as El Laberinto and the nearby soft bottoms were analysed. Species abundance and biomass data were obtained from the Arrastre Región Sur-Atlántica bottom trawl surveys carried out routinely from 1993 to 2009. A high biodiversity of megabenthic epifauna was found with a total of 272 species. Univariate community descriptors displayed similar values in zones inside and outside El Laberinto and in different seasons with the exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Surveys carried out in the Gulf of Cadiz (Sobrino et al 1996;Delgado et al 2013) and along the northern Iberian slope (Serrano et al 2011) have shown that G. melastomus, N. aequalis, and C. monstrosa are very abundant species. Within the Alboran Sea, these species are distributed differently at Cabo de Gata and in the eastern part of Alboran Island, where G. melastomus and N. aequalis are less abundant.…”
Section: Identified Assemblagesmentioning
confidence: 97%
See 1 more Smart Citation
“…Surveys carried out in the Gulf of Cadiz (Sobrino et al 1996;Delgado et al 2013) and along the northern Iberian slope (Serrano et al 2011) have shown that G. melastomus, N. aequalis, and C. monstrosa are very abundant species. Within the Alboran Sea, these species are distributed differently at Cabo de Gata and in the eastern part of Alboran Island, where G. melastomus and N. aequalis are less abundant.…”
Section: Identified Assemblagesmentioning
confidence: 97%
“…Two species recorded in this study have not been reported in the Mediterranean Sea beyond Cabo de Gata: Galeus atlanticus (Elasmobranchii) and L. sanzoi (Osteichthyes). The distribution of G. atlanticus extends westward from the Strait of Gibraltar to the Atlantic coast of the Southern Iberian Peninsula and Southern Portugal (Rey et al 2010); in fact, in Spanish waters of the Gulf of Cadiz, G. atlanticus is a dominant species, in terms of biomass, in several places sampled between 500 and 600 m depth (Delgado et al 2013). Its western distribution boundary is off Cabo St. Vicent (southwestern limit of Portugal).…”
Section: Ichthyofaunal Compositionmentioning
confidence: 99%
“…Several studies on sessile fauna have been undertaken to explore the biodiversity in different areas of the GoC (Delgado et al, 2013), revealing the occurrence of several sensitive and vulnerable habitats within the area, including cold-water corals or crinoid beds (Fonseca et al, 2014). However, to date, no quantitative investigation of the typology or abundance of litter artifacts or assessment of the impact of this phenomenon on deep-sea ecosystems have been undertaken in the GoC within the context of the specific oceanographic and marine traffic conditions in the area.…”
Section: Introductionmentioning
confidence: 99%
“…Cold seep areas are considered hotspots of biological and biodiversity singularity (Danovaro et al 2010, Mastrototaro et al 2010, Cunha et al 2013 and "Submarine structures caused by leaking gases, habitat 1180" are one of the very few marine habitats listed in Annex 1 (habitats for which a site of community importance may be declared) of the EU Habitat Directive (1992/43/EEC). Nevertheless, the information regarding the associated faunal communities is very limited in some deep-sea areas with seepage activity, such as that of the northern Gulf of Cádiz (GoC) (Rueda et al 2012b, Delgado et al 2013, Rueda et al 2016 in comparison with the current knowledge regarding those in the southern GoC (Oliver et al 2011, Cunha et al 2013.…”
Section: Introductionmentioning
confidence: 99%